Seasonal dynamics of mesozooplankton biomass over a sub‐Arctic continental shelf. Issue 13 (25th May 2021) - Silberberger, Marc J.; Renaud, Paul E.; Eiane, Ketil; Reiss, Henning
Abstract: Mesozooplankton research in high latitude ecosystems tends to focus on different life stages of Calanus spp. due to its biomass dominance and trophic roles. However, a complex seasonal succession of abundant smaller mesozooplankton taxa suggests that the ecological functioning of the mesozooplankton communities is more complicated. We studied the year‐round taxon‐specific biomass measurements and size distributions of mesozooplankton on a sub‐Arctic continental shelf based on formalin preserved samples. Our results confirm that Calanus spp. dominate the mesozooplankton biomass (81%). We show that commonly used length–weight relationships underestimate Calanus biomass in autumn and winter, and accordingly, a strong seasonal bias was introduced in our understanding of sub‐Arctic plankton communities. We observed two periods with considerable contribution of meroplankton, the planktonic larvae of benthic invertebrates, to the mesozooplankton biomass: (a) Cirripedia nauplii accounted for 17% of total biomass close to the coast in early April and (b) meroplankton comprised up to 12.7% of total biomass in late July. Based on these results, we suggest that meroplankton may play an ecologically important role in addition to their role in dispersal of benthic species. We conclude that the seasonal succession of the biomass of small‐sized holoplankton and meroplankton, often obscured by patterns in the Calanus biomass, should receive more attention as these smaller individuals are likely an important functional component of the pelagic food web. Abstract : Mesozooplankton play a key role as the major trophic link between the pelagic primary producers and higher trophic levels. Here, we show that meroplankton, the planktonic larvae of benthic invertebrates, contribute considerably to the biomass of the smallest mesozooplankton size fraction (<1 mm) during spring, the period of first feeding for most major fish stocks spawning in the sub‐Arctic. We suggest that meroplankton plays an ecologically important role, contributing to early feeding of commercial fish species.